EVALUASI KEBIJAKAN SISTEM ZONASI PPDB: ANTARA TUJUAN PEMERATAAN DAN REALITA KESENJANGAN MUTU SEKOLAH - Lukman El Hakim; Muhammad Melvin Naufal (JURNAL ILMIAH NUSANTARA, 2026)
The zoning-based New Student Admissions Policy (PPDB) was designed by the government as a concrete effort to ensure equal access, accelerate the distribution of educational quality, and eliminate the labels of "favorite schools" or "superior schools" in society. This article examines the dynamics of the implementation of the Zoning PPDB, which clearly presents two sides of implementation: success on the one hand and social polemics on the other. Its implementation requires continuous evaluation and improvement. Recommended strategic steps include routine teacher rotation, increasing the measurement of the percentage of achievement-track quotas, optimizing inter-institutional facility loans, and providing mentoring or special additional hours for students with below-average grades.